Nusikaltimai virtualioje erdvėje – šiuolaikiniai Iššūkiai ir prevencijos galimybės - Grigaitytė, Ugnė; Mackevičiūtė, Miglė (Vilnius University Open Series, 2020)
The article presents an analysis of the virtual crimes, its problematic aspects, inter alia, prevention opportunities. Discussing types of virtual crimes, content aspects in the context of nowadays challenges, illegal acts’ measures. Regulatory reviews at national, European Union and international level, considered by the competent intitutions, as well as case law. Convention on cybercrime, adopted in 2001, extensively covering and legally regulating crimes, commited through virtual space, a comparison with Lithuanian legislation, including criminal code. The work emphasizes latency of cybercrimes likewise the damages comparing with ordinary crimes.
Keywords: none